A Food and nutrition security policy for Antigua and Barbuda (St. John'sAG, 2012)
Incorporates new information and approaches with the aim of addressing the current and foreseeable critical food and nutrition problems of the country, viz. obesity, and Non-Communicable Diseases (NCDs) including hypertension, diabetes and some forms of cancer.
Keywords: FOOD POLICY